Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
How to differentiate partial derivatives?
I have the equation y''= 2y - xy' and i need to differentiate to obtain the third derivative but im not sure as to what the xy' term becomes when differentiated
2 Answers
- Dragon.JadeLv 75 years agoFavorite Answer
Hello,
NOTE: if my question is illegible, use a browser that displays Unicode characters like Firefox or Edge...
= = = = = = = = = = = = = = = =
βΊ Remember product law:
Β Β (πΒ·π)' = π'Β·π + πΒ·π'
So when π=π₯ and π=π¦' :
Β Β (π₯Β·π¦') = 1Β·π¦' + π₯Β·π¦" = π¦' + π₯Β·π¦"
βΊ Which means:
Β Β π¦" = 2π¦ β π₯Β·π¦'
yields by derivation:
Β Β π¦"' = 2π¦' β (π¦' + π₯Β·π¦") = 2π¦' β π¦' β π₯Β·π¦" = π¦' β π₯Β·π¦"
Regards,
Dragon.Jade :-)
- cidyahLv 75 years ago
y'' = 2y - xy'
y''' = 2y' - x y''
If it is partial derivative, xy' becomes x y'' when differentiated. else, it becomes y' + x y''